Increased professionalization and lower burnout scores were associated with structured residency training program: results of a cross sectional survey. Issue 1 (1st January 2021) - Olm, Michaela; Roos, Marco; Hapfelmeier, Alexander; Schneider, Dagmar; Gensichen, Jochen; Berberat, Pascal O.; Schneider, Antonius
ABSTRACT: The competence centre for Residency Training in Family Medicine Bavaria (CCRTB) was established to improve the quality of postgraduate medical education by offering training and mentoring programmes for residents, and by providing train-the-trainer and mentoring courses for supervisors. Beyond that, regional Residency Training Networks (RTN) on avoluntary basis were developed to facilitate structured and efficient clinical rotation programs. Primary aim was to investigate the burden of burnout and the development of professionalism among CCRTB-residencies within a cross-sectional study. Secondary aim was to evaluate differences between CCRTB-residents with and without participation in aregional RTN. Burnout was determined with the Maslach Burnout Inventory (MBI), comprising the scales emotional exhaustion, depersonalization, and personal accomplishment. Ambulatory professionalization was evaluated using the German Professional Scale (Pro-D), comprising the scales professionalism towards the patient, towards other professionals, towards society, and towards oneself. Statistical significance of group differences was calculated by nonparametric tests. Multivariable linear regression modelling was performed to estimate the independent impact of professionalization and RTN participation on burnout scores. 347 CRRTB residents in ambulatory postgraduate training were invited, 212 (61.1%) participated, and 197 (92.9%) were included in our analyses. Lower emotional exhaustion and depersonalization, and increased personal accomplishment was associated with increased professionalisation, which was significant for nearly all Pro-D scales (p ≤ 0.05). RTN residents showed higher professionalism towards the patient (p = 0.031), other professionals (p = 0.012), and towards the society (p = 0.007) than residents of unstructured programs, and higher levels of personal accomplishment (p < 0.05). Early and efficient professionalization might be akey to reduce burnout and to establish asatisfying career in family medicine. Train-the-trainer and mentoring concepts should be implemented regularly for the training of residents. Thus, increased engagement in medical didactics should be aprerequisite for accreditation as atraining practice for residents.